Mesocolic hernia after laparoscopic transverse colectomy: A case report. (2020) - Oshiro, Ken-ichi; Koinuma, Koji; Matsumiya, Misaki; Takami, Mariko; Inose, Satoshi; Kurihara, Katsumi; Horie, Hisanaga; Kawarai Lefor, Alan; Sata, Naohiro
Highlights: Internal hernias following laparoscopic colorectal resections are very rare. A mesenteric defect of the left transverse colon might be at higher risk of an internal hernia on anatomic grounds. We believe that a defect in the left transverse mesocolon require closure regardless of its size. Abstract: Introduction: Internal hernias are rare after laparoscopic colorectal resections. We report a patient with an internal hernia through a defect in the transverse mesocolon following laparoscopic resection. Presentation of case: A 52-year-old male underwent laparoscopic colectomy for transverse colon cancer and had an unremarkable postoperative course. Thirty days postoperatively, he presented to the emergency room with sudden onset abdominal pain and vomiting. Enhanced abdominal computed tomography scan showed strangulated small intestine in the left upper abdomen. An internal hernia through the mesenteric defect created during the recent colon resection was suspected, and emergency laparotomy was performed. One hundred thirty cm of small intestine was found herniated through a mesenteric defect. After repositioning the ischemic-appearing intestine, a 5 cm defect in the transverse mesocolon was found which had not been closed during the previous laparoscopic operation. No intestinal resection was needed, and the mesenteric defect closed with non-absorbable sutures. The post-operative course was unremarkable except for paralytic ileus, which resolved without further intervention. Discussion: The incidence of internal hernia through a mesenteric defect after laparoscopic colorectal resection is quite low. Therefore, routine closure of the mesenteric defect after laparoscopic colorectal resection is not required. However, a left sided defect in the transverse mesocolon might be at higher risk of causing an internal hernia on anatomic grounds. Conclusion: We believe that mesenteric defects should be closed after laparoscopic resection of the left side of transverse colon, regardless of their size.